Studies on the mechanical properties and corrosion behaviour of AI20Be20Fe10Si15Ti35 high entropy alloy produced by mechanical alloying and SPS sintering - Onawale, Omoyemi Temitope (Vaal University of Technology, 2022)
To meet structural, biomedical, and energy-saving application requirements, weight reduction is of utmost concern especially in the transportation sector because it is the feasible means of reducing fuel consumption as well as greenhouse gas emissions. The fabrication of light weight high entropy alloys (LWHEAs) using traditional design methods such as the addition of refractory elements or casting has proven that it is almost impossible to achieve the required properties in LWHEA. The spark plasma sintering (SPS) method was employed to consolidate wet and dry mechanically alloyed (MA) Al20Be20Fe10Si15Ti35. This is owing to the possibility of achieving desired mechanical properties and produce high-performance bulk HEAs with homogeneous and finer grains during the processing route, unlike the conventional casting techniques. The EDS, SEM and XRD examination that was conducted on both wet and dry milled alloy powders reveals a decomposition condition took place at temperatures of approx.. 2000C. We suspect that this is associated with a low melting Fe2Be17 phase, which becomes unstable with increase in temperature. This is in conformity with literature that highlights that the influence of Al and Fe on the performance of Be will depend upon which phases manifest. It has been established that volatility properties of ethanol and Fe must have aided sublimation tendency of wet milled alloy mix especially. This is in addition to evaporation tendency of Be powder. A thermo-analytical process was also conducted on both dry-milled and wet-milled alloy powder. This confirmed a decomposition leading to thermal expansion in both dry and wet milled alloy powder at a rapid rate from room temperature to ~150°C. Hence, Al20Be20Fe10Si15Ti35 milled powder is thermally unstable being the possible cause of premature sublimation that occurred during the sintering process.
M. Eng. (Department of Metallurgical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Mechanical properties; Mechanical alloying; Entropy alloy; Corrosion; Dissertations, Academic -- South Africa.; Alloys -- Mechanical properties.; Mechanical alloying.; Entropy.; Sintering.